2012
DOI: 10.1128/jb.00018-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functionally Important TonB-ExbD Periplasmic Domain Interactions In Vivo

Abstract: In Gram-negative bacteria, the cytoplasmic membrane proton-motive force energizes the active transport of TonB-dependent ligands through outer membrane TonB-gated transporters. In Escherichia coli , cytoplasmic membrane proteins ExbB and ExbD couple the proton-motive force to conformational changes in TonB, which are hypothesized to form the basis of energy transduction through direct contact with the transporters. While the role of ExbB is not well understood, contact between periplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 58 publications
1
43
1
Order By: Relevance
“…Whereas ExbD Ala92 was shown (15) to interact with TonB Ala150 (adjacent to our predicted region), it most likely contributes a different form of heterodimerization. A follow-up study by the same authors found that ExbD residues 92, 97, and 109 specifically and strongly cross-linked with TonB residues 150 to 212 (28). While at first these results may seem inconsistent with our phage display data, Ollis et al did not mutate the TonB residues identified here.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Whereas ExbD Ala92 was shown (15) to interact with TonB Ala150 (adjacent to our predicted region), it most likely contributes a different form of heterodimerization. A follow-up study by the same authors found that ExbD residues 92, 97, and 109 specifically and strongly cross-linked with TonB residues 150 to 212 (28). While at first these results may seem inconsistent with our phage display data, Ollis et al did not mutate the TonB residues identified here.…”
Section: Discussioncontrasting
confidence: 55%
“…However, considering the nonphysiological conditions (pH 3 and low salt) and a propensity for protein aggregation, it is not surprising that this study did not reflect in vivo evidence of ExbD-TonB interactions (15,23,(25)(26)(27). Postle and coworkers identified periplasmic regions involved in ExbD and TonB interactions by disulfide crosslinking (26,28). In the absence of TonB, the same ExbD regions tend to promote their homodimerization (26).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we engineered Cys substitutions in each of two TonB system proteins to identify sites of interaction via disulfide cross-linking (49)(50)(51)(52)(53)(54). Because the exact sites of interaction between the two proteins are unknown, many combinations of cysteine substitutions must be engineered in order to map the interaction interface.…”
Section: Discussionmentioning
confidence: 99%